2015
DOI: 10.1007/s11085-015-9534-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of a Dispersion-Strengthened Powder Metallurgical FeCrAl Alloy in the Presence of O2 at 1,100 °C: The Influence of Water Vapour

Abstract: The oxidation behaviour of the FeCrAl alloy Kanthal Ò APMT in O 2 ? N 2 and O 2 ? N 2 ? H 2 O environments at 1,100°C was investigated using thermogravimetry and detailed analyses of the scale morphology with SEM/EDX and STEM/EDX. Wrought FeCrAl alloy Kanthal Ò AF was used as a reference. Exposure time was up to 168 h. Water vapour influenced the early oxide growth kinetics. This effect is explained in terms of water acting as an oxidant, simultaneously with O 2 . During later stages of the exposures, H 2 O ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
(62 reference statements)
2
11
0
Order By: Relevance
“…95 % N 2 . The chosen pre-oxidation conditions were studied more in detail by Hellström et al [18,19]. A short description of the obtained alumina scales can be found below.…”
Section: Resultsmentioning
confidence: 99%
“…95 % N 2 . The chosen pre-oxidation conditions were studied more in detail by Hellström et al [18,19]. A short description of the obtained alumina scales can be found below.…”
Section: Resultsmentioning
confidence: 99%
“…The 6 wt% of Al in the investigated alloy is above the minimum Al concentration suggested for the formation of Al-rich oxide layers on FeCrAl alloys [33] and, indeed, the formation of an Al-rich oxide layer was evident after the different preoxidation treatments (Figures 1, 3 and 4). It is well documented [19][20][21]24,25,[33][34][35][36][37][38][39][40] that formation of any of the Al2O3 polymorphs (α-, γ-, δ-, θ-phase) is influenced by variables such as H2O in the environment, temperature and time. Earlier studies [22,24,32] have reported that α-Al2O3 formation is favoured at temperatures above 1050 o C, while at lower temperatures metastable polymorphs (δ-, γ-, θ-Al2O3) predominate.…”
Section: The Influence Of Preoxidation Conditionsmentioning
confidence: 99%
“…This work is expected to lead to the development of correlations between microstructure and mechanical properties of APMT TM steel. This is relevant because recent studies [1,4,7] on this steel mostly focused on the oxidation/corrosion characteristics of this steel, not on its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%